Fourier-Chebyshev Coefficients and Gauss-Turán Quadrature with Chebyshev Weight (Journal of Computational Mathematics, 2003)
The main purpose of this paper is to derive an explicit expression for Fourier-Chebyshev coefficient $A_{kn}(f)=\frac{\displaystyle 2}{\displaystyleπ}\int_{-1}^1f(x)T_{kn}(x)\frac{\displaystyle dx}{\displaystyle \sqrt{1-x^2}},k,n\in N_0$, which is initiated by L. Gori and C. A. Micchelli.
Keywords: Fourier-Chebyshev coefficient; Gauss-Turán quadrature.